SP Column Analysis in Testing the Strength and Sustainability of Industrial Building Sub-Structures - Lukman Arief; Heru Setiyo Cahyono; Ruli Saefudin (DEARSIP : Journal of Architecture and Civil, 2026)
Analysis of sub-structures in cigarette factory buildings with concrete construction is essential to ensure the overall stability, safety, and efficiency of the building, especially in resisting static loads as well as dynamic loads from industrial machinery operations. This study aims to quantitatively evaluate the design capacity of lower structure elements, especially pedestals and foot plates and their repeating specifications, in order to ensure the safety and efficiency limits of materials that support sustainability. Methods: The analysis was performed using SP Column software that relies on the interaction surface diagram (P-M) method to validate the cross-sectional capacity of reinforced concrete against a combination of axial forces and bending moments, combined with computational analytical mechanics for shear and ground stress. The computational results show that the foot plate with an effective thickness of 0.22 m has a shear strength of 519.21 kN, far exceeding the shear force that occurs (284.267 kN). The ratio of precision measured pedestal reinforcement  at 4%. Evaluation of steel performance proves the operating voltage is safe in the elastic region (below the modulus of 200,000 MPa). In addition, the area of the reinforced slab (113 mm²) exceeds the theoretical requirements of the structural analysis (66,987 mm²), which is an effective surplus in securing the position of the main reinforcement and resisting concrete cracks due to temperature reduction. The design of the lower structure of this factory building is proven to be daktail, safe, and legally compliant with the loading regulations of SNI 1727:2013 and the structural concrete requirements of SNI 2847:2019 (as a correction to the citation of SNI 1726 in the initial data). This computational optimization of the reinforcement ratio also prevents the waste of building materials, in line with the principles of sustainable industrial engineering.